ANALISIS PREFERENSI NASABAH DALAM UPAYA PENINGKATAN CASA (CURRENT ACCOUNT SAVING ACCOUNT) PADA PT BANK CENTRAL ASIA, Tbk. KOTA MEDAN - Silsilya Lee; Nazaruddin; Purnomo Wibowo, Rulianda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted at PT Bank Central Asia, Tbk., Medan City, to analyze customer preferences in selecting savings or current account products (CASA). The study is motivated by the strategic importance of increasing CASA as part of BCA’s sustainable funding agenda to support credit expansion and maintain healthy asset growth. Nonetheless, the achievement of the CASA volume target at PT Bank Central Asia, Tbk., Medan City declined in 2024, with actual performance reaching only 53.94% of the established target. This gap between the target and the realization of low-cost fund mobilization underscores the need to identify the product attributes most strongly considered by customers in deposit placement decisions. Conjoint analysis was employed to examine how respondents make choices based on combinations of multiple product attributes. The research variables comprised interest rates, administrative fees, service quality, transaction security, and ease of digital access. Respondents’ preference data were analyzed to derive the relative importance of each attribute and to determine the dominant factors shaping customer selection of CASA products. The findings indicate that administrative fees (26.908%) and interest rates (26.564%) have the highest relative importance among the evaluated attributes. This suggests that customers prioritize cost considerations and financial benefits when choosing savings or current account products. Accordingly, CASA growth strategies should place greater emphasis on managing the administrative fee structure and enhancing the competitiveness of interest rates, while strengthening ease of digital access, service quality, and transaction security as supporting factors to improve customer preference and loyalty.